Phosphine-catalyzed nucleophilic ring opening of cyclopropenones with sulfoximines to access N-α,β-unsaturated acyl sulfoximines - Thete, Kishor R.; Vara, Vijay; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
Herein, we describe the formation of biologically relevant N-alpha,beta-unsaturated acyl sulfoximines via phosphine-catalyzed C-C bond activation of cyclopropenones with weakly nucleophilic sulfoximines. The new process does not require a transition metal or external oxidant and displays high regioselectivity and exclusive E-selectivity. Other salient features of the method are a broad substrate scope, high compatibility with various functional groups, and high atom economy.